Improving students’ performance with time management skills - Pundir, Sudhir kumar (Universal Research Reports, 2017)
The study's goal was to find out whether students' ability to manage their time had any effect on their academic performance. When it comes to a person's overall performance and accomplishments, time management is very vital. But the way people manage their time to fit their everyday lives or make it flow smoothly with their routines is a common thread in all of them. Students will be more likely to succeed if they are placed in an atmosphere that is conducive to learning. However, a student's ability to manage his or her time is a factor in being a successful student. Students who want to succeed need to be able to manage their time well. There are students who are unable to manage their time well, which has a severe impact on both their personal lives and their academic performance. Students' everyday habits and activities influence how they use their free time in college. Students' time management might have an impact on their stress levels since they have to balance their academic and personal responsibilities.